Analisis Teknik Renang Gaya Bebas pada Atlet Renang - Harmoko Harmoko; Ever Sovensi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
This study aimed to describe freestyle swimming techniques in Athlete Noren Tirta Buana Musi Rawas. This research includes qualitative descriptive research types. Data collection in this study using Interview, Observation and Documentation techniques. The source of the data collected in the study is 1 Object which is a training ground in Noren Tirta Buana Musi Rawas. Data retrieval is carried out in the afternoon, after the data collected data is observed directly. The findings obtained by the researchers showed that freestyle swimming techniques are seen from aspects of body position, arm movement, leg movement, breathing movements, and coordination in Athlete Noren Tirta Buana Musi Rawas from 15 participants who took observation tests, interviews and documentation. In conclusion, the average freestyle swimming techniques athletes are in accordance with the theoretical study where there are 11 people who have done the movement correctly and 4 more people are still wrong in doing foot movements. Keywords: Athlete Noren Tirta Buana Musi Rawa, Engineering Freestyle Swimming